Tinjauan Yuridis terhadap Kesiapan Regulasi Pasar Modal Indonesia dalam Menghadapi Risiko Sistemik Akibat Krisis Ekonomi Global - Nervia, Clara; Wardhana, Kresentia Aiko; Talim, Talitha Livia (Anthology: Inside Intellectual Property Rights, 2025)
The capital market plays a crucial role in the national financial system as an intermediary and a source of long-term financing. In the era of globalization, Indonesia's capital market is increasingly exposed to systemic risks triggered by global economic crises, such as the US-China trade war and the 2008 financial crisis. This research aims to review the readiness of Indonesia’s capital market regulations in facing systemic risks from a juridical perspective. The method used is a normative juridical approach, analyzing Law No. 8 of 1995 on Capital Market, OJK regulations, and other relevant policies. The findings reveal that although the current regulations provide a legal foundation for supervision and investor protection, they are not fully adaptive to global systemic risks. Macroprudential provisions are still limited, and regulatory responses tend to be reactive. Therefore, strengthening regulations through the integration of macroprudential principles, improved institutional coordination, and risk-based policy reforms is necessary. This will enable Indonesia’s capital market to be more resilient in facing global pressures and maintaining stability as part of the national financial system.